A fast and reliable method for detecting SNP rs67384697 (Hsa‐miR‐148a binding site) by a single run of allele‐specific real‐time PCR. (15th July 2020) - Malnati, Mauro S.; Biswas, Priscilla; Ugolotti, Elisabetta; Di Marco, Eddi; Sironi, Francesca; Parolini, Francesca; Garbarino, Lucia; Mazzocco, Michela; Zipeto, Donato; Biassoni, Roberto
Abstract : Surface expression of human leukocyte antigen (HLA)‐class I molecules is critical for modulating T/natural killer lymphocytes' effector functions. Among HLA molecules, HLA‐C, the most recently evolved form of class I antigens, is subjected to both transcriptional and multiple post‐transcriptional regulation mechanisms affecting its cell surface expression. Among the latter a region placed in the 3′ untranslated region of HLA‐C transcript contains the single nucleotide polymorphism (SNP) rs67384697 "G‐ins/del" that has been found to be strictly associated with surface levels of HLA‐C allomorphs because of the effect on the binding site of a microRNA (Hsa‐miR‐148a). Higher expression of HLA‐C has been proved to influence HIV‐1 infection via a better control of viremia and a slower disease progression. More importantly, the analysis of SNP rs67384697 "G‐ins/del" combined with the evaluation of the HLA‐Bw4/‐Bw6 C1/C2 supratype, as well as the killer immunoglobulin‐like receptor genetic asset, has proved to be pivotal in defining the status of Elite Controllers in the Caucasian population. Here we describe a new reliable and fast method of allele‐specific real‐time PCR to monitor the integrity/disruption of the binding site of the microRNA Hsa‐miR‐148a in a high‐throughput format that can be easily applied to studies involving large cohorts of individuals.